2009
DOI: 10.2174/1874210600903010048
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Two Different Drinking Water Fluoride Levels, Dental Fluorosis and Bone Mineral Density of Children

Abstract: This field study included the whole population of children aged 10–15 years (77 from a 0.19 mg/L F area; 89 from a 3.00 mg/L F area), with similar nutritional, dietary habits and similar ethnic and socioeconomic status. The fluoride concentration in the drinking water, the bone mineral content, the bone density and the degree of dental fluorosis were determined. The left radius was measured for bone width, bone mineral content, and bone mineral density. The mean fluorosis score was 1.3 in the low fluoride area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
(35 reference statements)
1
15
0
2
Order By: Relevance
“…Associations of fluoride intake with children's cortical bone measures outcome measures robust. Our results are consistent with several ecological studies (i.e., studies that did not assess fluoride intakes at the individual level, but instead compared bone measures among children living in communities with fluoridated versus non-fluoridated water) which found no significant differences in bone outcomes by fluoridation status (5,6,9). Furthermore, a previous analysis of the IFS/IBDS data showed only modest relationships between DXA scans of hip, spine, and whole body and fluoride intakes at age 11 (10), with even weaker associations with DXA outcomes at age 15 (22).…”
Section: Sm Levy Et Alsupporting
confidence: 91%
“…Associations of fluoride intake with children's cortical bone measures outcome measures robust. Our results are consistent with several ecological studies (i.e., studies that did not assess fluoride intakes at the individual level, but instead compared bone measures among children living in communities with fluoridated versus non-fluoridated water) which found no significant differences in bone outcomes by fluoridation status (5,6,9). Furthermore, a previous analysis of the IFS/IBDS data showed only modest relationships between DXA scans of hip, spine, and whole body and fluoride intakes at age 11 (10), with even weaker associations with DXA outcomes at age 15 (22).…”
Section: Sm Levy Et Alsupporting
confidence: 91%
“…Dual-energy x-ray absorptiometry (DXA) for assessment of bone outcomes showed that Canadian young adult women and Swedish adolescents residing in optimally fluoridated areas had significantly higher mineral density in lumbar vertebra and the whole body, respectively, than those in non-fluoridated areas (Arnold et al, 1997;Bratteb et al, 2002). A recent study compared left radial singlephoton absorptiometry bone measures of South African adolescents in residents from areas with 0.19-ppm vs. 3.00-ppm water fluoride levels (Grobler et al, 2009). In the 14-to 15-year-old age group only, radial BMD was significantly higher for children from high-vs. low-fluoride areas.…”
mentioning
confidence: 99%
“…The different results between this project and other studies are probably due in part to the different period‐specific fluoride intakes and densitometry techniques used. Another investigation found significant differences in left radius BMD of 14‐ to 15‐year‐old adolescents living in an area with 3 ppm water fluoride levels from those exposed to < 0.2 ppm fluoride, but not for 10‐ to 11‐year‐olds or 12‐ to 13‐year‐olds …”
Section: Discussionmentioning
confidence: 96%
“…year-olds or 12-to 13-year-olds. 10 Previous studies that investigated the effects of fluoride on bone measures were mostly ecological, where they did not assess fluoride intakes at the individual level, but compared bone measures of participants living in communities with different levels of water fluoride.…”
Section: Discussionmentioning
confidence: 99%